Glass-ceramics, method for manufacturing same, glass device, electronic product
Patent Information
- Application Number
- CN202510462232.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-11
- Publication Date
- 2026-10-20
AI Technical Summary
[0004]本申请的目的在于提供一种微晶玻璃及其制备方法,以及一种玻璃器件,一种电子产品,旨在解决现有微晶玻璃的弹性模量、透过率与离子交换性能难以协同提升的问题
[0051]本申请玻璃器件,采用的上述微晶玻璃同时具有较高的弹性模量、透过率和离子交换性能,使其在玻璃器件中展现出独特的综合优势,尤其适用于对力学强度、光学性能和耐用性要求苛刻的场景。具体地,高弹性模量,材料刚度高,可减少玻璃器件在受力时的弯曲或形变,适合制造超薄但抗弯折的部件。本申请玻璃器件,通过微晶玻璃“强(高模量)-透(高透过)-韧(可强化)”三位一体特性,突破传统玻璃器件强度与透光矛盾)或蓝宝石(成本高、难加工)的局限,成为高端玻璃器件的理想选择,推动电子、光学、医疗等领域的创新迭代。
Smart Images

Figure BDA0005357920560000011 
Figure BDA0005357920560000051 
Figure BDA0005357920560000151
Abstract
Description
Technical Field
[0001] This application belongs to the field of glass technology, and particularly relates to a microcrystalline glass and its preparation method, as well as a glass device and an electronic product. Background Technology
[0002] The rapid iteration of smartphones and other electronic products has placed higher demands on the mechanical properties of cover glass, such as drop resistance and scratch resistance. Traditional electronic product cover glass is mainly made of high-alumina glass; however, existing high-alumina glass can no longer meet the needs, necessitating the development of new products to achieve breakthroughs. Currently, cover glass for electronic products is gradually being replaced by microcrystalline glass, which has higher strength. However, existing microcrystalline glass cover glass still suffers from problems such as low elastic modulus and low scratch resistance, resulting in low glass strength and a risk of breakage during use. Furthermore, microcrystalline glass with a low elastic modulus has poor resistance to deformation, resulting in insufficient strength even when thinner, making it difficult to achieve lightweight and thinner designs. Moreover, the bulk mechanical, optical, and ion exchange properties of microcrystalline glass are interdependent; improving one property often leads to a decline in others. Existing methods for increasing the elastic modulus of microcrystalline glass result in a decrease in glass transmittance and ion exchange performance.
[0003] Therefore, how to synergistically improve the elastic modulus, transmittance and ion exchange performance of glass-ceramics is an urgent problem to be solved. Summary of the Invention
[0004] The purpose of this application is to provide a microcrystalline glass and its preparation method, as well as a glass device and an electronic product, aiming to solve the problem that the elastic modulus, transmittance and ion exchange performance of existing microcrystalline glasses are difficult to improve in a synergistic way.
[0005] To achieve the above-mentioned objectives, the technical solution adopted in this application is as follows:
[0006] The first aspect of this application provides a microcrystalline glass, which, calculated as a molar percentage of oxides, comprises the following components:
[0007]
[0008] The main crystalline phase of the microcrystalline glass does not contain alkali metals.
[0009] The microcrystalline glass provided in this application, through the rational control of the distribution ratio of each oxide component in the glass composition, not only achieves controllable precipitation of crystalline phases, resulting in the precipitation of high elastic modulus crystalline phases and promoting the improvement of the elastic modulus of the microcrystalline glass; it also effectively controls the composition and structure of the residual glass, improves the network connectivity of the residual glass phase, and promotes the improvement of the elastic modulus of the microcrystalline glass. This achieves a synergistic improvement in the elastic modulus, transmittance, and ion exchange performance of the microcrystalline glass in a glass composition containing high levels of alkali metal ions. This allows the microcrystalline glass to simultaneously possess high elastic modulus, high ion exchange performance, and high transmittance. The main crystalline phase of the microcrystalline glass in this application does not contain alkali metal ions, so the ion exchange process does not lead to crystal amorphization, thus improving the ion exchange efficiency of the microcrystalline glass. By controlling the crystallinity of the crystalline phase to regulate the depth of the ion exchange layer, a synergistic improvement in crystallinity and ion exchange layer depth is achieved.
[0010] As some possible implementations of the microcrystalline glass of this application, the main crystalline phase in the microcrystalline glass includes Mg2SiO4. The precipitated Mg2SiO4 crystalline phase does not contain Al. 3+ Ion exchange with alkali metal ions does not lead to amorphization, and the residual Mg in the glass matrix after crystallization... 2+ The reduced content improves ion exchange efficiency. As the crystallinity of Mg₂SiO₄ increases, the ion exchange depth also increases, achieving a synergistic improvement in both crystallinity and ion exchange depth. Furthermore, the high elastic modulus of the Mg₂SiO₄ crystalline phase enhances the elastic modulus of the glass-ceramic. This results in the glass-ceramic simultaneously possessing high elastic modulus, transmittance, and ion exchange performance.
[0011] As some possible implementations of the microcrystalline glass of this application, the average grain size of the crystalline phase in the microcrystalline glass is not higher than 50 nm; in this case, the average grain size of the crystalline phase in the microcrystalline glass is controlled below 50 nm (nanometer level), which can significantly improve the overall performance of the microcrystalline glass.
[0012] As some possible implementations of the microcrystalline glass of this application, the crystallinity of the microcrystalline glass is 35% to 60%. In this case, an ideal synergistic effect can be formed between the glass phase and the crystalline phase.
[0013] As some possible implementations of the microcrystalline glass of this application, in which the absolute difference between the molar percentage of Al2O3 and the total molar percentage of alkali metal oxides is not higher than 2%, the alkali metal oxides including Li2O, Na2O, K2O, and Cs2O. In this case, the residual glass matrix can have a higher degree of network connectivity, thereby improving the elastic modulus of the residual glass matrix.
[0014] As some possible implementations of the microcrystalline glass of this application, the ratio of Na₂O to Li₂O in the microcrystalline glass is greater than 0 and not higher than 0.3. In this case, it is beneficial to improve the ion exchange performance of the microcrystalline glass.
[0015] As some possible implementations of the microcrystalline glass of this application, the ratio of MgO to SiO2 in the microcrystalline glass is not less than 0.6 and not more than 1. In this case, it is more conducive to the precipitation of the Mg2SiO4 crystalline phase.
[0016] As some possible implementations of the microcrystalline glass of this application, the microcrystalline glass comprises, in molar percentage of oxides, the following components: 44% SiO2, 10% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 30% MgO, and 4% TiO2.
[0017] As some possible implementations of the microcrystalline glass of this application, the microcrystalline glass comprises, in molar percentage of oxides, the following components: 42% SiO2, 12% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 30% MgO, and 4% TiO2.
[0018] As some possible implementations of the microcrystalline glass of this application, the microcrystalline glass comprises, in molar percentage of oxides: 40% SiO2, 14% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 30% MgO, and 4% TiO2.
[0019] As some possible implementations of the microcrystalline glass of this application, the microcrystalline glass comprises, in molar percentage of oxides, 40% SiO2, 17% Al2O3, 2% Na2O, 14% Li2O, 25% MgO, and 2% TiO2.
[0020] As some possible implementations of the microcrystalline glass of this application, the microcrystalline glass comprises, in molar percentage of oxides, the following components: 41% SiO2, 14% Al2O3, 1% Na2O, 14% Li2O, 1% Cs2O, 27% MgO, and 2% TiO2.
[0021] As some possible implementations of the microcrystalline glass of this application, the microcrystalline glass comprises, in molar percentage of oxides, the following components: 40% SiO2, 10% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 34% MgO, and 4% TiO2.
[0022] As some possible implementations of the microcrystalline glass of this application, the microcrystalline glass comprises, in molar percentage of oxides, the following components: 41% SiO2, 12% Al2O3, 3% Na2O, 10% Li2O, 1% K2O, 29% MgO, and 4% TiO2.
[0023] As some possible implementations of the microcrystalline glass of this application, the microcrystalline glass comprises, in molar percentage of oxides, the following components: 41% SiO2, 12% Al2O3, 1% Na2O, 10% Li2O, 3% K2O, 29% MgO, and 4% TiO2.
[0024] As some possible implementations of the microcrystalline glass of this application, the microcrystalline glass comprises, in molar percentage of oxides, the following components: 41% SiO2, 12% Al2O3, 1% Na2O, 10% Li2O, 3% Cs2O, 29% MgO, and 4% TiO2.
[0025] As some possible implementations of the microcrystalline glass of this application, the microcrystalline glass comprises, in molar percentage of oxides, the following components: 45% SiO2, 10% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 30% MgO, and 4% TiO2.
[0026] As some possible implementations of the microcrystalline glass of this application, the microcrystalline glass comprises, in molar percentage of oxides, the following components: 40% SiO2, 12% Al2O3, 4% Na2O, 10% Li2O, 1% K2O, 29% MgO, and 4% TiO2.
[0027] As some possible implementations of the microcrystalline glass of this application, the microcrystalline glass comprises, in molar percentage of oxides, 43% SiO2, 15% Al2O3, 1% Na2O, 12% Li2O, 25% MgO, and 4% TiO2.
[0028] As some possible implementations of the microcrystalline glass of this application, the microcrystalline glass comprises the following components, calculated by molar percentage of oxides: 42% SiO2, 11% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 1% Cs2O, 30% MgO, and 4% TiO2.
[0029] As some possible implementations of the microcrystalline glass of this application, the microcrystalline glass comprises, in molar percentage of oxides, the following components: 42% SiO2, 11% Al2O3, 1% Na2O, 10% Li2O, 2% Cs2O, 30% MgO, and 4% TiO2.
[0030] As some possible implementations of the microcrystalline glass of this application, the microcrystalline glass comprises, in molar percentage of oxides, the following components: 40% SiO2, 10% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 35% MgO, and 3% TiO2.
[0031] As some possible implementations of the microcrystalline glass of this application, the microcrystalline glass comprises, in molar percentage of oxides, the following components: 43% SiO2, 10% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 30% MgO, and 5% TiO2.
[0032] As some possible implementations of the microcrystalline glass of this application, the microcrystalline glass also includes a clarifying agent. This agent removes bubbles and unmelted particles from the glass melt, ensuring that the molten glass is free of visible defects.
[0033] As some possible implementations of the microcrystalline glass of this application, the clarifying agent includes at least one of Sb2O3, As2O3, SnO2, Na2SO4, K2SO4, Li2SO4, NaNO3, and KNO3.
[0034] As some possible implementations of the microcrystalline glass of this application, the molar percentage content of the clarifying agent in the microcrystalline glass is 0.1% to 1%. In this case, the content of the clarifying agent can effectively remove gases from the microcrystalline glass and ensure the performance of the microcrystalline glass.
[0035] As some possible implementations of the microcrystalline glass of this application, the microcrystalline glass, with a thickness of 0.7 mm, has a transmittance of not less than 89% for a wavelength of 550 nm. The microcrystalline glass of this application has a high transmittance.
[0036] As some possible implementations of the microcrystalline glass of this application, the elastic modulus of the microcrystalline glass is 115 GPa to 130 GPa. The microcrystalline glass of this application has a high elastic modulus.
[0037] As some possible implementations of the microcrystalline glass of this application, the compressive stress at a depth of 50 micrometers from the surface of the microcrystalline glass is 113 MPa to 165 MPa. In this case, the mechanical reliability and environmental adaptability of the material can be significantly optimized through fine control of the stress gradient.
[0038] As some possible implementations of the microcrystalline glass of this application, the stress layer depth of the microcrystalline glass is 100 μm to 130 μm. In this case, the overall performance of the material can be significantly improved through the reasonable distribution of surface compressive stress.
[0039] Secondly, this application provides a method for preparing microcrystalline glass, comprising the following steps:
[0040] The raw materials, calculated by the molar percentage of oxides, include 40%–45% SiO2, 10%–17% Al2O3, 10%–14% Li2O, 1%–4% Na2O, 0%–3% K2O, 0%–3% Cs2O, 25%–35% MgO, and 2%–5% TiO2. These components are then mixed to form a substrate glass.
[0041] The substrate glass is heat-treated to crystallize it, resulting in a microcrystalline glass, wherein the main crystalline phase of the microcrystalline glass does not contain alkali metals.
[0042] The method for preparing microcrystalline glass provided in this application involves preparing a substrate glass comprising 40%–45% SiO2, 10%–17% Al2O3, 10%–14% Li2O, 1%–4% Na2O, 0%–3% K2O, 0%–3% Cs2O, 25%–35% MgO, and 2%–5% TiO2, followed by heat treatment to crystallize the substrate glass, thereby obtaining microcrystalline glass. The preparation process is simple and suitable for large-scale industrial production and application. In the prepared microcrystalline glass, the main crystalline phase does not contain alkali metal ions, and the ion exchange process does not lead to amorphization of the crystals, thus improving the ion exchange efficiency of the microcrystalline glass. By rationally controlling the distribution ratio of each oxide component in the glass composition, not only can the crystalline phase be precipitated in a controlled manner, resulting in the precipitation of a high elastic modulus crystalline phase and promoting the improvement of the elastic modulus of the glass-ceramic, but the composition and structure of the residual glass can also be effectively controlled, improving the network connectivity of the residual glass phase and achieving a synergistic improvement in the elastic modulus, transmittance and ion exchange performance of the glass-ceramic.
[0043] As some possible implementations of the method for preparing the microcrystalline glass of this application, the melting temperature for preparing the substrate glass is 1400℃~1650℃. Under this temperature condition, it is possible to ensure that the various raw material components are fully melted and mixed.
[0044] As some possible implementations of the preparation method of the microcrystalline glass of this application, the annealing conditions for preparing the substrate glass include annealing at a temperature of 450℃ to 650℃ for 1 hour to 10 hours. Under these conditions, residual stress can be eliminated, cracking can be prevented, the microstructure can be stabilized, and the performance can be optimized.
[0045] As some possible implementations of the preparation method of the microcrystalline glass of this application, the heat treatment is a one-step heat treatment, including treatment at a temperature of 620℃~800℃ for 1h~10h. In this case, nucleation (crystal nucleation) and crystallization (crystal growth) processes are completed simultaneously within a single temperature range, eliminating the need for segmented temperature control, simplifying equipment operation, and reducing process complexity.
[0046] As some possible implementations of the preparation method of the microcrystalline glass of this application, the heat treatment is a two-step heat treatment, including treatment at a temperature of 580℃~660℃ for 1h~10h, followed by treatment at a temperature of 660℃~800℃ for 1h~20h. In this case, nucleation treatment (forming crystal nuclei) is first performed at a lower temperature, and then crystallization (crystal growth) is completed at a higher temperature.
[0047] As some possible implementations of the preparation method of the microcrystalline glass of this application, after the heat treatment, the method further includes immersing the microcrystalline glass sheet in an ion-exchange molten salt to chemically strengthen the microcrystalline glass through an ion-exchange process. Enhancing the mechanical properties of the microcrystalline glass through ion exchange can also form a compressive stress layer on the surface of the microcrystalline glass, thereby improving its impact and scratch resistance; and altering the chemical composition and microstructure of the microcrystalline glass surface can improve its surface properties.
[0048] As some possible implementations of the method for preparing the microcrystalline glass of this application, the ion-exchange molten salt includes at least one of NaNO3 molten salt and KNO3 molten salt.
[0049] As some possible implementations of the method for preparing the microcrystalline glass of this application, the ion exchange process is carried out at a temperature of 340℃ to 520℃ for a duration of 2h to 8h. Under these conditions, it is possible to sufficiently ensure the chemical strengthening of the microcrystalline glass through the ion exchange process.
[0050] Thirdly, this application provides a glass device, which is made of the above-mentioned microcrystalline glass and / or the above-mentioned microcrystalline glass.
[0051] The glass device of this application utilizes the aforementioned microcrystalline glass, which simultaneously possesses high elastic modulus, transmittance, and ion exchange performance, exhibiting unique comprehensive advantages among glass devices. It is particularly suitable for applications with stringent requirements for mechanical strength, optical performance, and durability. Specifically, the high elastic modulus and high material stiffness reduce bending or deformation of the glass device under stress, making it suitable for manufacturing ultra-thin yet bend-resistant components. This glass device, through the integrated characteristics of "strength (high modulus) - transparency (high transmittance) - toughness (strengthenability)" of microcrystalline glass, overcomes the limitations of traditional glass devices (the contradiction between strength and light transmission) or sapphire (high cost and difficult processing), becoming an ideal choice for high-end glass devices and driving innovation and iteration in the fields of electronics, optics, and medicine.
[0052] Fourthly, this application provides an electronic product that includes the aforementioned glass device.
[0053] The electronic products of this application include the aforementioned glass devices, which simultaneously possess high elastic modulus, transmittance, and ion exchange performance, thereby improving the application safety, stability, and service life of the electronic products.
[0054] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application. Attached Figure Description
[0055] Figure 1 This is a schematic flowchart of the method for preparing microcrystalline glass provided in the embodiments of this application;
[0056] Figure 2 The XRD pattern of the microcrystalline glass provided in Embodiment 1 of this application is shown.
[0057] Figure 3 This application provides a transmittance curve of microcrystalline glass in Embodiment 1;
[0058] Figure 4 Example 9 of this application provides an ion exchange stress curve for a microcrystalline glass.
[0059] Figure 5 Example 9 of this application provides a curve showing the relationship between the crystallinity of Mg2SiO4 and the depth of the ion exchange layer in a glass-ceramic.
[0060] Figure 6 Examples 3, 4, 7, and 12 of this application provide curves showing the relationship between Na2O content and ion exchange layer depth in microcrystalline glass. Detailed Implementation
[0061] To make the technical problems, technical solutions, and beneficial effects of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.
[0062] In this application, the term "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural. The character " / " generally indicates that the preceding and following related objects have an "or" relationship.
[0063] In this application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0064] It should be understood that in the various embodiments of this application, the order of the above processes does not imply the order of execution. Some or all steps may be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.
[0065] The terminology used in the embodiments of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of this application. The singular forms “a,” “the,” and “the” used in the embodiments of this application and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise.
[0066] The term "ordinary glass" primarily consists of silicon dioxide (SiO2), supplemented with sodium carbonate (Na2CO3), limestone (CaCO3), and other materials. It is produced by rapidly cooling after high-temperature melting, without undergoing a crystallization process, and is therefore an amorphous solid (with disordered atomic arrangement). Because ordinary glass is completely amorphous and its internal atomic arrangement is disordered, it is prone to cracking due to stress concentration.
[0067] The term "microcrystalline glass" refers to glass formed by adding nucleating agents (such as TiO2, ZrO2, P2O5, etc.) to ordinary glass components, through controlled crystallization. Its structure is a glass matrix. +The uniformly distributed microcrystalline phase exhibits both amorphous and crystalline properties. The superior performance of glass-ceramics stems from the synergistic effect of their crystal-glass composite structure: the crystalline phase endows glass-ceramics with high strength, heat resistance, and chemical stability; while the residual glass phase reduces structural defects and inhibits crack propagation by filling grain boundary voids and optimizing interfacial bonding.
[0068] The term "alkali metals" refers to elements in Group 1 (Group IA) of the periodic table (excluding hydrogen), including lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), and francium (Fr). Alkali metal ions are formed when an alkali metal atom loses one of its outermost electrons. + Monovalent cations, such as Li + Na + K + Alkali metals are chemically reactive, readily losing electrons and exhibiting strong reducing properties. Their reactivity order is: Li <Na<K<Rb<Cs。
[0069] In the term "CS50," CS stands for Compressed Stress. CS50 refers to the compressive stress at a depth of 50 micrometers from the surface of the tempered glass, measured in MPa. This is an important parameter for tempered glass, used to measure its strengthening effect and impact resistance. Generally, a higher CS50 value indicates better strengthening and stronger impact resistance.
[0070] The term "DOL" stands for Depth of Layer, referring to the depth of the compressive stress layer formed in tempered glass through chemical strengthening (such as ion exchange). This depth is the distance from the glass surface to the point where the compressive stress drops to zero. It represents the stress layer depth of the glass, measured in micrometers (μm). This is an important parameter of tempered glass, closely related to its strengthening effect and impact resistance. Generally, a deeper DOL means a thicker compressive stress layer, thus providing better resistance to external impacts and scratches, improving the glass's safety and lifespan.
[0071] Currently, from a market perspective, high-alumina glass is the primary material for cover glass in traditional smartphones and other electronic products. However, traditional high-alumina glass can no longer meet the demands of rapid product iteration for improved mechanical properties such as drop resistance and scratch resistance in cover glass. Therefore, there is an urgent need to develop new glass products to achieve breakthroughs. Currently, microcrystalline glass covers with lithium disilicate and lithium feldspar as the main crystalline phases exhibit excellent drop resistance and are already used in the cover glass of many electronic products. However, existing microcrystalline glass covers still suffer from low scratch resistance and low elastic modulus, which not only leads to low glass strength and easy breakage during use, but also results in poor resistance to deformation due to insufficient elastic modulus, leading to insufficient strength even at thinner thicknesses, making it difficult to achieve lightweight and thinner designs. Therefore, there is an urgent need to develop new types of microcrystalline glass with high elastic modulus for better application in the cover glass of electronic products.
[0072] To alleviate the problem of low elastic modulus in glass-ceramics, research has found that improving the elastic modulus of glass-ceramics mainly involves two approaches: precipitation of high-strength crystalline phases and control of residual glass phases. Currently, high elastic modulus glass-ceramics are primarily achieved by precipitating high elastic modulus crystals (such as spinel and cordierite) and increasing crystal content. However, the bulk mechanical, optical, and ion-exchange properties of glass-ceramics are interdependent; improving one property often leads to a decrease in others. For example, the elastic modulus of glass-ceramics can usually be improved by increasing the crystallinity of high-strength crystalline phases, but this increase in crystallinity is accompanied by enhanced light scattering, resulting in decreased transmittance. Furthermore, to improve the elastic modulus of glass-ceramics, the base glass composition often has a relatively low or even absent alkali metal ion content, leading to lower ion-exchange performance.
[0073] Furthermore, compared to ordinary glass, the ion exchange performance of glass-ceramics is more complex and challenging, primarily because the mobility of alkali metal ions in the crystalline phase is lower than that in the glass phase. Currently, ion exchange performance of glass-ceramics is typically improved by controlling ion exchange conditions, such as adjusting the molten salt ratio, employing a two-step ion exchange method, increasing the ion exchange temperature, and extending the ion exchange time. However, these methods for controlling ion exchange in glass-ceramics are not only costly, but the improvement in ion exchange performance achieved by increasing temperature and extending time is not continuous; after reaching a certain level, the ion exchange performance will decrease. This is because increasing the ion exchange temperature or extending the time is accompanied by relaxation of the glass surface structure, reducing surface compressive stress and deep stress, thus decreasing ion exchange performance. In addition, for glass-ceramics containing alkali metal ions in the crystalline phase, increasing the ion exchange temperature or extending the time may also cause amorphization of the crystals, further reducing the strength of the glass-ceramics. For glass-ceramics in which alkali metal ions participate in crystallization, the depth of the ion exchange layer usually decreases with the increase of crystallinity, resulting in a decline in ion exchange performance. However, the improvement of the glass body strength requires a high degree of crystallinity, making it difficult to achieve a synergistic improvement in crystallinity and ion exchange layer depth.
[0074] Therefore, how to synergistically improve the elastic modulus, transmittance and ion exchange performance of glass-ceramics is an urgent problem to be solved.
[0075] Based on the above considerations, and in order to synergistically improve the elastic modulus, transmittance, and ion exchange performance of glass-ceramics, this application proposes a glass-ceramic comprising, by molar percentage of oxides: 40%–45% SiO2, 10%–17% Al2O3, 10%–14% Li2O, 1%–4% Na2O, 0%–3% K2O, 0%–3% Cs2O, 25%–35% MgO, and 2%–5% TiO2.
[0076] In such glass-ceramics, the elastic modulus is enhanced by crystallization with high elastic modulus and by improving the network connectivity of the residual glass phase through the composition and structural design of the residual glass matrix. Simultaneously, the ion exchange efficiency of the glass-ceramics is improved by precipitating alkali-metal-free crystals, and the depth of the ion exchange layer is controlled by crystallinity, achieving a synergistic improvement in both crystallinity and ion exchange layer depth.
[0077] For ease of understanding, this application is specifically described through the following embodiments. It should be understood that the following embodiments are only used to further illustrate the solution of this application and are not intended to limit the scope of this application.
[0078] In a first aspect, embodiments of this application provide a microcrystalline glass, which, calculated by the molar percentage of oxides, comprises the following components:
[0079]
[0080] The main crystalline phase in glass-ceramics does not contain alkali metals.
[0081] Thus, the microcrystalline glass provided in this application, through the rational control of the distribution ratio of each oxide component in the glass composition, can not only achieve controllable precipitation of the crystalline phase, precipitating a high elastic modulus crystalline phase and promoting the improvement of the elastic modulus of the microcrystalline glass; it can also effectively control the composition and structure of the residual glass, improve the network connectivity of the residual glass phase, and promote the improvement of the elastic modulus of the microcrystalline glass. This achieves a synergistic improvement in the elastic modulus, transmittance, and ion exchange performance of the microcrystalline glass in a glass composition containing a high level of alkali metal ions. This allows the microcrystalline glass to simultaneously possess high elastic modulus, high ion exchange performance, and high transmittance. In the microcrystalline glass of this application, the main crystalline phase does not contain alkali metal ions, and the ion exchange process does not lead to crystal amorphization, improving the ion exchange efficiency of the microcrystalline glass. By controlling the crystallinity of the crystalline phase to regulate the depth of the ion exchange layer, a synergistic improvement in crystallinity and ion exchange layer depth is achieved.
[0082] In some possible implementations, the main crystalline phase in the glass-ceramic includes Mg2SiO4. In the embodiments of this application, the main crystalline phase in the glass-ceramic is Mg2SiO4 through compositional control. In this case, the precipitated Mg2SiO4 crystalline phase does not contain Al. 3+ Ion exchange with alkali metal ions does not lead to amorphization, and the residual Mg in the glass matrix after crystallization... 2+ The reduced content improves ion exchange efficiency. As the crystallinity of Mg₂SiO₄ increases, the ion exchange depth also increases, achieving a synergistic improvement in both crystallinity and ion exchange depth. Furthermore, the high elastic modulus of the Mg₂SiO₄ crystalline phase enhances the elastic modulus of the glass-ceramic. This results in the glass-ceramic simultaneously possessing high elastic modulus, transmittance, and ion exchange performance.
[0083] In the microcrystalline glass of this application, SiO2, as the main component forming the glass network structure, plays a decisive role in the stability of the glass and is also a key component for the precipitation of Mg2SiO4 crystals. Through systematic experimental research and performance characterization, this invention draws the following important conclusions: the crystallization behavior of Mg2SiO4 is significantly negatively correlated with the degree of connection of the glass network. Specifically, when the degree of connection of the glass network decreases, that is, when the network structure tends to be loose, it is more conducive to the precipitation of Mg2SiO4 crystals; at the same time, this loose network structure can also effectively inhibit crystal growth, promote the refinement of Mg2SiO4 grains, and thus significantly improve the optical transmittance of the microcrystalline glass. However, too low a SiO2 content will cause the degree of connection of the glass network to decrease excessively, resulting in a decrease in glass forming ability and seriously affecting the stability of the material. Too high a SiO2 content will lead to a significant increase in glass viscosity, which not only increases the difficulty and cost of the melting process, but also inhibits the crystallization process of Mg2SiO4, and easily leads to coarsening of crystal size, reducing the transmittance of the microcrystalline glass. Taking into account various factors, the molar percentage of SiO2 in this application embodiment is controlled between 40% and 45%. For example, the molar percentage of SiO2 can be any typical but non-limiting point value or a range between any two point values, such as 40%, 41%, 42%, 43%, 44%, 45%.
[0084] In the microcrystalline glass of this application, Al2O3, as a network intermediate oxide, plays a unique structural role in the glass system. Its coordination state and functional properties depend on the glass composition: when alkali metal ions (R... + ) and alkaline earth metal ions (R2) + When the total amount of Al exceeds the Al2O3 content, Al 3+ It exists in a four-coordinate form, acting as a network former; conversely, when R... + and R2 + When the total amount is lower than the Al2O3 content, some Al 3+Al2O3 exists in a five- or six-coordinate form, transforming into a network modifier. In the embodiments of this application, increasing the Al2O3 content improves the connectivity of the glass network, thereby enhancing the stability and mechanical properties of the material. However, excessively high Al2O3 content can lead to an overly dense glass network, increasing the difficulty of melting and inhibiting the crystallization process of Mg2SiO4. On the other hand, since [AlO4] tetrahedra have a larger volume than [SiO4] tetrahedra, they can effectively expand the network gaps, providing more unobstructed migration channels for alkali metal ions, thereby significantly improving ion exchange performance. Considering all aspects, the molar percentage of Al2O3 in the embodiments of this application is controlled between 10% and 17%. For example, the molar percentage of Al2O3 can be any typical but non-limiting point value or a range between any two points, such as 10%, 12%, 14%, 15%, 16%, or 17%.
[0085] In the microcrystalline glass of this application, Li₂O, as a network modifier oxide, plays multiple key roles in the glass system. Its content significantly affects the material's structure and properties. First, increasing the Li₂O content reduces the connectivity of the glass network, making the network structure more porous, which promotes the precipitation of small-sized Mg₂SiO₄ crystals, thereby improving the optical transmittance of the microcrystalline glass. Second, Li₂O has a significant fluxing effect; increasing its content can effectively lower the melting point and viscosity of the glass, improving the material's meltability and processing performance. Furthermore, increasing the Li₂O content can enhance the glass's ion exchange properties, significantly improving the material's mechanical strength through the ion exchange process. However, excessive Li₂O can excessively disrupt the glass network structure, leading to decreased material stability and reduced glass-forming ability. After comprehensive consideration, the molar percentage of Li2O in this application embodiment is controlled between 10% and 14%. For example, the molar percentage of Li2O can be any typical but non-limiting point value or a range between any two point values, such as 10%, 11%, 12%, 13%, 14%.
[0086] In the microcrystalline glass of this application embodiment, Na₂O is a network modifier, and its function is similar to that of Li₂O, but Na₂O… + Its electronegativity is less than that of Li +When Na₂O partially replaces Li₂O, the size of Mg₂SiO₄ crystals can be reduced, resulting in higher transmittance of the glass-ceramic. The introduction of Na₂O into the glass-ceramic composition can effectively control the depth of the ion exchange layer. With an appropriate amount of Na₂O, the substitution of Li by Na within the glass-ceramic during ion exchange occurs via a shorter path and higher efficiency compared to Na-Li exchange in molten salt. However, excessively high Na₂O content leads to an unstable glass network structure and difficulties in glass forming. In this application, the molar percentage of Na₂O is controlled between 1% and 4%. Exemplarily, the molar percentage of Na₂O can be any typical but non-limiting value, such as 1%, 2%, 3%, or 4%, or a range between any two values.
[0087] In the microcrystalline glass embodiments of this application, K₂O and Cs₂O, as network-modifying oxides, play a similar but more significant role to Na₂O in the glass system. Because K… + and Cs + It has more than Na + The lower electronegativity and stronger electron-donating ability of K2O and Cs2O can more effectively weaken the glass network structure, further refining the grain size of Mg2SiO4 and thus improving the transmittance of the glass-ceramic. However, excessively high contents of K2O and Cs2O lead to decreased glass stability and difficulties in glass casting. In the glass-ceramic embodiments of this application, the contents of K2O and Cs2O range from 0 to 3%. Exemplarily, the molar percentage of K2O can be any typical but non-limiting point value or a range between any two points, such as 0, 0.2%, 0.5%, 1%, 2%, 3%. The molar percentage of Cs2O can be any typical but non-limiting point value or a range between any two points, such as 0, 0.2%, 0.5%, 1%, 2%, 3%.
[0088] In the glass-ceramics of this application, MgO is a key component for the precipitation of Mg2SiO4 crystals, and its content has a decisive influence on the crystallization behavior and properties of the material. Increasing the MgO content significantly promotes the crystallization process of Mg2SiO4, mainly because MgO provides the structural units required for crystal formation and lowers the crystallization activation energy. However, excessively high MgO content leads to a decrease in the stability of the glass network structure, specifically manifested as reduced glass-forming ability, increased crystallization tendency, and a narrowing of the forming process window. Furthermore, insufficient MgO content not only inhibits the precipitation of Mg2SiO4 but also leads to coarsening of crystal size, increasing light scattering loss, thereby reducing the optical transmittance of the glass-ceramics. In this application, the molar percentage of MgO is controlled between 25% and 35%. Exemplarily, the molar percentage of MgO can be any typical but non-limiting point value or a range between any two points, such as 25%, 26%, 28%, 30%, 31%, 32%, 34%, 34%.
[0089] In the microcrystalline glass of this application, TiO2, as a highly efficient nucleating agent, plays a crucial role in promoting the uniform precipitation of Mg2SiO4 crystals. Its mechanism of action is mainly reflected in the fact that TiO2 precipitates before Mg2SiO4 during heat treatment, forming heterogeneous nucleation sites, thereby significantly reducing the crystallization activation energy of Mg2SiO4 and promoting uniform nucleation and growth of crystals. However, excessively high TiO2 content not only reduces the stability of the glass but also... + The dd electron transitions cause visible light absorption, leading to glass coloration and decreased transmittance; while excessively low TiO2 content results in insufficient nucleation density, causing coarsening of Mg2SiO4 crystal size and increasing light scattering loss. In this application, the molar percentage of MgO is controlled between 2% and 5%. Exemplarily, the molar percentage of MgO can be any typical but non-limiting point value or a range between any two points, such as 2%, 3%, 4%, or 5%.
[0090] In some possible implementations, the average grain size of the crystalline phase in the glass-ceramic is no higher than 50 nm. In this case, controlling the average grain size of the crystalline phase below 50 nm (nanoscale) significantly improves the overall performance of the glass-ceramic. Firstly, grain refinement significantly increases the strength and hardness of the material; nanocrystals hinder dislocation movement, giving the glass-ceramic higher strength and hardness. Furthermore, fine grains can suppress crack propagation, improve the fracture toughness of the glass-ceramic, and reduce the risk of brittle fracture. Secondly, the grain size is much smaller than the visible light wavelength (400 nm–700 nm), reducing light scattering and allowing the glass-ceramic to maintain high strength while possessing excellent light transmittance. The nanocrystalline phase can also adjust the overall refractive index of the material, expanding its applications in optical devices. Simultaneously, nanocrystals are more stable at high temperatures, with greater resistance to grain boundary migration, preventing material weakening due to grain growth, reducing the coefficient of thermal expansion of the glass-ceramic, improving thermal shock resistance, and enhancing thermal stability.
[0091] In some embodiments, the average grain size of the crystalline phase in the glass-ceramic can be 10 nm to 50 nm, specifically any typical but non-limiting point value or an interval between any two point values such as 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 40 nm, 50 nm.
[0092] In some possible implementations, the crystallinity of the glass-ceramic is 35%–60%. In this case, an ideal synergistic effect can be formed between the glass phase and the crystalline phase. This crystallinity provides high strength, high hardness, and wear resistance, while the amorphous network in the glass phase can absorb energy, inhibit crack propagation, and improve the fracture toughness of the material. A suitable proportion of crystalline phase can reduce stress concentration, delay the initiation of fatigue cracks, and extend the lifespan of the glass-ceramic.
[0093] In some possible embodiments, the absolute difference between the molar percentage of Al2O3 and the total molar percentage of alkali metal oxides (R2O) in the glass-ceramic is no higher than 2%, where the alkali metal oxides include Li2O, Na2O, K2O, and Cs2O. That is, -2% ≤ Al2O3 - (Li2O + Na2O + K2O + Cs2O) ≤ 2%. In the embodiments of this application, in order to improve the elastic modulus of the residual glass matrix by increasing the degree of network connectivity, the relationship between Al2O3 and alkali metal oxides (R2O) is required to satisfy -2 ≤ Al2O3 - R2O ≤ 2%. When Al2O3 - R2O < -2%, the alkali metal content is too high, the non-bridging oxygen content in the residual glass matrix increases, and the degree of network connectivity decreases; when Al2O3 - R2O > 2%, some Al2O3... 3+exist in the form of network modifiers, which also reduce the connectivity of the network. Both will lead to a decrease in the elastic modulus of the residual glass phase. Exemplarily, Al₂O₃-R₂O can be any typical but non-limiting point value such as -2%, -1%, 0%, 1%, 2%, etc., or an interval value between any two of the foregoing point values.
[0094] In some possible embodiments, in the glass-ceramic, the ratio of Na₂O to Li₂O is greater than 0 and no more than 0.3; that is, 0<Na₂O / Li₂O≤0.3. In the embodiments of the present application, when 0<Na₂O / Li₂O≤0.3, it is beneficial to improve the ion exchange performance of the glass-ceramic. If the composition does not contain Na₂O, the depth of the ion exchange layer of the glass-ceramic is relatively low; if the content of Na₂O is too high, the surface compressive stress generated by ion exchange will decrease. Exemplarily, Na₂O / Li₂O can be any typical but non-limiting point value such as 0.1, 0.2, 0.3, etc., or an interval value between any two of the foregoing point values.
[0095] In some possible embodiments, in the glass-ceramic, the ratio of MgO to SiO₂ is no less than 0.6 and no more than 1, that is, 0.6≤MgO / SiO₂≤1. In the embodiments of the present application, when 0.6≤MgO / SiO₂≤1, the precipitation of the Mg₂SiO₄ crystal phase is more facilitated. When the ratio is too low, the difficulty of Mg₂SiO₄ crystal precipitation increases; while when the ratio is too high, the stability of the glass-ceramic will be reduced. Exemplarily, MgO / SiO₂ can be any typical but non-limiting point value such as 0.6, 0.7, 0.8, 0.9, 1, etc., or an interval value between any two of the foregoing point values.
[0096] In some possible embodiments, calculated by mole percentage of oxides, the glass-ceramic includes the following components: 44% of SiO₂, 10% of Al₂O₃, 1% of Na₂O, 10% of Li₂O, 1% of K₂O, 30% of MgO, 4% of TiO₂. In this case, the elastic modulus of the glass-ceramic is 119 GPa, the compressive stress at a depth of 50 micrometers from the surface of the glass-ceramic (CS50) is 122 MPa, the depth of the stress layer (DOL) is 108 μm, and the Vickers hardness after ion exchange is 866 kgf / mm 2 .
[0097] In some possible embodiments, the glass-ceramic comprises, by molar percentage of oxides: 42% SiO2, 12% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 30% MgO, and 4% TiO2. In this case, the glass-ceramic has an elastic modulus of 120 GPa, a compressive stress (CS50) of 143 MPa at a depth of 50 μm from the surface, a stress layer depth (DOL) of 118 μm, and a Vickers hardness of 878 kgf / mm² after ion exchange. 2 .
[0098] In some possible embodiments, the glass-ceramic comprises, by molar percentage of oxides: 40% SiO2, 14% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 30% MgO, and 4% TiO2. In this case, the glass-ceramic has an elastic modulus of 124 GPa, a compressive stress (CS50) of 152 MPa at a depth of 50 μm from the surface, a stress layer depth (DOL) of 114 μm, and a Vickers hardness of 895 kgf / mm² after ion exchange. 2 .
[0099] In some possible embodiments, the glass-ceramic comprises, by molar percentage of oxides: 40% SiO2, 17% Al2O3, 2% Na2O, 14% Li2O, 25% MgO, and 2% TiO2. In this case, the glass-ceramic has an elastic modulus of 127 GPa, a compressive stress (CS50) of 163 MPa at a depth of 50 μm from the surface, a stress layer depth (DOL) of 125 μm, and a Vickers hardness of 908 kgf / mm² after ion exchange. 2 .
[0100] In some possible embodiments, the glass-ceramic comprises, by molar percentage of oxides: 41% SiO2, 14% Al2O3, 1% Na2O, 14% Li2O, 1% Cs2O, 27% MgO, and 2% TiO2. In this case, the glass-ceramic has an elastic modulus of 122 GPa, a compressive stress (CS50) of 146 MPa at a depth of 50 μm from the surface, a stress layer depth (DOL) of 119 μm, and a Vickers hardness of 889 kgf / mm² after ion exchange. 2 .
[0101] In some possible embodiments, the glass-ceramic comprises, by molar percentage of oxides: 40% SiO2, 10% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 34% MgO, and 4% TiO2. In this case, the glass-ceramic has an elastic modulus of 118 GPa, a compressive stress (CS50) of 113 MPa at a depth of 50 μm from the surface, a stress layer depth (DOL) of 101 μm, and a Vickers hardness of 855 kgf / mm² after ion exchange. 2 .
[0102] In some possible embodiments, the glass-ceramic comprises, by molar percentage of oxides: 41% SiO2, 12% Al2O3, 3% Na2O, 10% Li2O, 1% K2O, 29% MgO, and 4% TiO2. In this case, the glass-ceramic has an elastic modulus of 117 GPa, a compressive stress (CS50) of 121 MPa at a depth of 50 μm from the surface, a stress layer depth (DOL) of 128 μm, and a Vickers hardness of 863 kgf / mm² after ion exchange. 2 .
[0103] In some possible embodiments, the glass-ceramic comprises, by molar percentage of oxides: 41% SiO2, 12% Al2O3, 1% Na2O, 10% Li2O, 3% K2O, 29% MgO, and 4% TiO2. In this case, the glass-ceramic has an elastic modulus of 116 GPa, a compressive stress (CS50) of 140 MPa at a depth of 50 μm from the surface, a stress layer depth (DOL) of 116 μm, and a Vickers hardness of 860 kgf / mm² after ion exchange. 2 .
[0104] In some possible embodiments, the glass-ceramic comprises, by molar percentage of oxides: 41% SiO2, 12% Al2O3, 1% Na2O, 10% Li2O, 3% Cs2O, 29% MgO, and 4% TiO2. In this case, the glass-ceramic has an elastic modulus of 115 GPa, a compressive stress (CS50) of 135 MPa at a depth of 50 μm from the surface, a stress layer depth (DOL) of 117 μm, and a Vickers hardness of 851 kgf / mm² after ion exchange. 2 .
[0105] In some possible embodiments, the glass-ceramic comprises, by molar percentage of oxides: 45% SiO2, 10% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 30% MgO, and 4% TiO2. In this case, the glass-ceramic has an elastic modulus of 120 GPa, a compressive stress (CS50) of 121 MPa at a depth of 50 μm from the surface, a stress layer depth (DOL) of 110 μm, and a Vickers hardness of 868 kgf / mm² after ion exchange. 2 .
[0106] In some possible embodiments, the glass-ceramic comprises, by molar percentage of oxides: 40% SiO2, 12% Al2O3, 4% Na2O, 10% Li2O, 1% K2O, 29% MgO, and 4% TiO2. In this case, the glass-ceramic has an elastic modulus of 129 GPa, a compressive stress (CS50) of 169 MPa at a depth of 50 μm from the surface, a stress layer depth (DOL) of 122 μm, and a Vickers hardness of 921 kgf / mm² after ion exchange. 2 .
[0107] In some possible embodiments, the glass-ceramic comprises, by molar percentage of oxides: 43% SiO2, 15% Al2O3, 1% Na2O, 12% Li2O, 25% MgO, and 4% TiO2. In this case, the glass-ceramic has an elastic modulus of 114 GPa, a compressive stress (CS50) of 112 MPa at a depth of 50 μm from the surface, a stress layer depth (DOL) of 130 μm, and a Vickers hardness of 851 kgf / mm² after ion exchange. 2 .
[0108] In some possible embodiments, the glass-ceramic comprises, by molar percentage of oxides: 42% SiO2, 11% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 1% Cs2O, 30% MgO, and 4% TiO2. In this case, the glass-ceramic has an elastic modulus of 122 GPa, a compressive stress (CS50) of 154 MPa at a depth of 50 μm from the surface, a stress layer depth (DOL) of 116 μm, and a Vickers hardness of 887 kgf / mm² after ion exchange. 2 .
[0109] In some possible embodiments, the glass-ceramic comprises, by molar percentage of oxides: 42% SiO2, 11% Al2O3, 1% Na2O, 10% Li2O, 2% Cs2O, 30% MgO, and 4% TiO2. In this case, the glass-ceramic has an elastic modulus of 117 GPa, a compressive stress (CS50) of 123 MPa at a depth of 50 μm from the surface, a stress layer depth (DOL) of 110 μm, and a Vickers hardness of 863 kgf / mm² after ion exchange. 2 .
[0110] In some possible embodiments, the glass-ceramic comprises, by molar percentage of oxides: 40% SiO2, 10% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 35% MgO, and 3% TiO2. In this case, the glass-ceramic has an elastic modulus of 115 GPa, a compressive stress (CS50) of 122 MPa at a depth of 50 μm from the surface, a stress layer depth (DOL) of 109 μm, and a Vickers hardness of 855 kgf / mm² after ion exchange. 2 .
[0111] In some possible embodiments, the glass-ceramic comprises, by molar percentage of oxides: 43% SiO2, 10% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 30% MgO, and 5% TiO2. In this case, the glass-ceramic has an elastic modulus of 115 GPa, a compressive stress (CS50) of 118 MPa at a depth of 50 μm from the surface, a stress layer depth (DOL) of 103 μm, and a Vickers hardness of 852 kgf / mm² after ion exchange. 2 .
[0112] In some possible implementations, the glass-ceramic also includes a clarifying agent. In this case, the addition of a clarifying agent to the glass-ceramic can remove bubbles (such as O2, CO2, SO2, N2, etc.) from the glass melt, ensuring that the molten glass is free of visible defects.
[0113] In some possible implementations, the clarifying agent includes at least one selected from Sb₂O₃, As₂O₃, SnO₂, Na₂SO₄, K₂SO₄, Li₂SO₄, NaNO₃, and KNO₃. These clarifying agents can decompose at high temperatures to generate gases (such as O₂), which carry small bubbles upwards and are discharged, ensuring that the molten glass is free of visible defects. They can also react with oxygen in the molten glass to generate CO₂ bubbles, adsorbing and removing impurity gases.
[0114] In some possible implementations, the molar percentage of the clarifying agent in the glass-ceramic is 0.1% to 1%. In this case, the amount of clarifying agent is sufficient to effectively remove gases from the glass-ceramic, ensuring its performance. Exemplarily, the molar percentage of the clarifying agent in the glass-ceramic can be any typical but non-limiting point value or a range between any two points, such as 0.1%, 0.2%, 0.3%, 0.5%, 0.6%, 0.8%, or 1.0%.
[0115] In some possible implementations, the microcrystalline glass, with a thickness of 0.7 mm, has a transmittance of not less than 89% for a wavelength of 550 nm. The microcrystalline glass in the embodiments of this application has a high transmittance. Exemplarily, the transmittance of the microcrystalline glass, with a thickness of 0.7 mm, for a wavelength of 550 nm can be any typical but non-limiting point value or a range between any two point values, such as 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%.
[0116] In some possible implementations, the elastic modulus of the glass-ceramic is between 115 GPa and 130 GPa. The glass-ceramic in the embodiments of this application has a high elastic modulus. Exemplarily, the elastic modulus of the glass-ceramic can be any typical but non-limiting point value or a range between any two point values, such as 115 GPa, 116 GPa, 117 GPa, 118 GPa, 119 GPa, 120 GPa, 121 GPa, 122 GPa, 123 GPa, 124 GPa, 125 GPa, 126 GPa, 127 GPa, 128 GPa, 129 GPa, and 130 GPa.
[0117] In some possible implementations, the compressive stress (CS50) at a depth of 50 micrometers from the surface of the glass-ceramic is 113 MPa to 165 MPa. In this case, the mechanical reliability and environmental adaptability of the material can be significantly optimized through fine-tuning of the stress gradient. A transition buffer layer is formed between the high surface stress and the internal tensile stress, effectively preventing crack propagation into the material, especially in the presence of surface micro-damage (scratches, impact pits), significantly slowing the crack propagation rate. The moderate compressive stress of CS50 can offset the excessive concentration of internal tensile stress (usually caused by the difference in thermal expansion between the surface compression layer and the interior), avoiding sudden overall brittle fracture due to excessive tensile stress. This suppresses the propagation of medium-deep cracks, improves dynamic load life, enhances damage resistance, reduces the risk of internal tensile stress, and enhances environmental adaptability; it balances the strengthening effect with processing feasibility, supporting high-precision applications. For example, the CS50 of the microcrystalline glass can be any point value or an interval value between any two point values, such as 113MPa, 115MPa, 118MPa, 120MPa, 125MPa, 130MPa, 135MPa, 140MPa, 145MPa, 150MPa, 155MPa, 160MPa, 165MPa, etc.
[0118] In some possible implementations, the depth of the stress layer (DOL) of the microcrystalline glass is 100 μm to 130 μm. In this case, the overall performance of the material can be significantly improved through the rational distribution of surface compressive stress. The surface compressive stress layer can effectively counteract the tensile stress induced by external loads, inhibit the propagation of surface microcracks inward, and prevent brittle fracture of the material. A thicker compressive layer can disperse impact energy, reducing the risk of the material fracturing upon drop or impact. High surface compressive stress (usually accompanied by increased hardness) can resist scratches from sharp objects, reduce visible scratches during daily use, and extend service life. For example, the stress layer depth of the microcrystalline glass can be any typical but non-limiting point value or an interval between any two point values, such as 100μm, 112μm, 113μm, 114μm, 115μm, 116μm, 117μm, 118μm, 119μm, 120μm, 121μm, 122μm, 123μm, 124μm, 125μm, 126μm, 127μm, 128μm, 129μm, 130μm.
[0119] In some possible embodiments, the glass-ceramic, with a thickness of 0.7 mm, has a transmittance of not less than 89% for a wavelength of 550 nm; the elastic modulus of the glass-ceramic is 115 GPa to 130 GPa; the compressive stress at a depth of 50 micrometers from the surface of the glass-ceramic is 113 MPa to 165 MPa; and the stress layer depth of the glass-ceramic is 100 μm to 130 μm. The glass-ceramic simultaneously possesses high elastic modulus, transmittance, and ion exchange performance.
[0120] Secondly, embodiments of this application provide a method for preparing microcrystalline glass, as shown in the attached figure. Figure 1 As shown, it includes the following steps:
[0121] S10. Based on the molar percentage of oxides, obtain raw materials corresponding to the following components: 40%–45% SiO2, 10%–17% Al2O3, 10%–14% Li2O, 1%–4% Na2O, 0%–3% K2O, 0%–3% Cs2O, 25%–35% MgO, and 2%–5% TiO2, and mix them to form a substrate glass;
[0122] S20. Heat-treat the substrate glass to crystallize it, thereby obtaining glass-ceramics, wherein the main crystalline phase of the glass-ceramics does not contain alkali metals.
[0123] The method for preparing microcrystalline glass provided in this application involves preparing a substrate glass comprising 40%–45% SiO2, 10%–17% Al2O3, 10%–14% Li2O, 1%–4% Na2O, 0%–3% K2O, 0%–3% Cs2O, 25%–35% MgO, and 2%–5% TiO2. The substrate glass is then crystallized through heat treatment to obtain microcrystalline glass. The preparation process is simple and suitable for large-scale industrial production and application. In the prepared microcrystalline glass, the main crystalline phase does not contain alkali metal ions, and the ion exchange process does not lead to amorphization of the crystal, thus improving the ion exchange efficiency of the microcrystalline glass. By rationally controlling the distribution ratio of each oxide component in the glass composition, not only can the crystalline phase be precipitated in a controlled manner, resulting in the precipitation of a high elastic modulus crystalline phase and promoting the improvement of the elastic modulus of the glass-ceramic, but the composition and structure of the residual glass can also be effectively controlled, improving the network connectivity of the residual glass phase and achieving a synergistic improvement in the elastic modulus, transmittance and ion exchange performance of the glass-ceramic.
[0124] In step S10 above:
[0125] In some possible implementations, the raw materials corresponding to each component are mixed in proportion, and after melting, clarification and homogenization, forming, and annealing, a base glass is obtained. Clarification removes air bubbles (such as O2, CO2, SO2, N2, etc.) from the glass melt, ensuring that the molten glass is free of visible defects. Homogenization eliminates compositional differences (such as streaks, phase separation, or unmelted particles) in the glass melt, achieving a uniform distribution of chemical composition and physical state. Concentration gradients are gradually eliminated through the thermal motion of ions at high temperatures (Fick's law of diffusion). Natural convection (driven by temperature gradient) or forced convection (such as mechanical stirring and bubbling) within the melting furnace promotes melt flow and mixing. Annealing, through stress relief, structural homogenization, and performance optimization, enables the microcrystalline glass to possess both high strength, high stability, and processability.
[0126] In some possible implementations, the melting temperature for preparing the substrate glass is 1400°C to 1650°C; this temperature ensures that the raw material components are fully melted and mixed. Exemplarily, the melting temperature for preparing the substrate glass can be any typical but non-limiting point value or a range between any two points, such as 1400°C, 1450°C, 1500°C, 1550°C, 1600°C, or 1650°C.
[0127] In some possible implementations, the annealing conditions for preparing the substrate glass include annealing at a temperature of 450°C to 650°C for 1 to 10 hours. Under these conditions, residual stress can be eliminated, cracking prevented, the microstructure stabilized, performance optimized, surface glass phase densification promoted, porosity and microcracks reduced, and the penetration of corrosive media such as water, acids, and alkalis blocked. Exemplarily, the annealing temperature for preparing the substrate glass can be any typical but non-limiting point value or a range between any two points, such as 450°C, 500°C, 550°C, 600°C, or 650°C, and the annealing time can be any typical but non-limiting point value or a range between any two points, such as 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, or 10 hours.
[0128] In some possible implementations, the main crystalline phase in the glass-ceramic includes Mg2SiO4.
[0129] In some possible implementations, the average grain size of the crystalline phase in the glass-ceramic is no higher than 50 nm; the crystallinity of the glass-ceramic is 35% to 60%.
[0130] In some possible implementations, in the glass-ceramic, the absolute difference between the molar percentage of Al2O3 and the total molar percentage of alkali metal oxides is not higher than 2%; the ratio of Na2O to Li2O is greater than 0 and not higher than 0.3; the ratio of MgO to SiO2 is not less than 0.6 and not higher than 1, wherein the alkali metal oxides include Li2O, Na2O, K2O and Cs2O.
[0131] In some possible implementations, the glass-ceramic comprises, by molar percentage of oxides: 44% SiO2, 10% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 30% MgO, and 4% TiO2.
[0132] In some possible implementations, the glass-ceramic comprises, by molar percentage of oxides: 42% SiO2, 12% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 30% MgO, and 4% TiO2.
[0133] In some possible implementations, the glass-ceramic comprises, by molar percentage of oxides: 40% SiO2, 14% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 30% MgO, and 4% TiO2.
[0134] In some possible implementations, the glass-ceramic comprises, by molar percentage of oxides: 40% SiO2, 17% Al2O3, 2% Na2O, 14% Li2O, 25% MgO, and 2% TiO2.
[0135] In some possible implementations, the glass-ceramic comprises, by molar percentage of oxides: 41% SiO2, 14% Al2O3, 1% Na2O, 14% Li2O, 1% Cs2O, 27% MgO, and 2% TiO2.
[0136] In some possible implementations, the glass-ceramic comprises, by molar percentage of oxides: 40% SiO2, 10% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 34% MgO, and 4% TiO2.
[0137] In some possible implementations, the glass-ceramic comprises, by molar percentage of oxides: 41% SiO2, 12% Al2O3, 3% Na2O, 10% Li2O, 1% K2O, 29% MgO, and 4% TiO2.
[0138] In some possible implementations, the glass-ceramic comprises, by molar percentage of oxides: 41% SiO2, 12% Al2O3, 1% Na2O, 10% Li2O, 3% K2O, 29% MgO, and 4% TiO2.
[0139] In some possible implementations, the glass-ceramic comprises, by molar percentage of oxides: 41% SiO2, 12% Al2O3, 1% Na2O, 10% Li2O, 3% Cs2O, 29% MgO, and 4% TiO2.
[0140] In some possible implementations, the glass-ceramic also includes a clarifying agent. In some embodiments, the clarifying agent includes at least one selected from Sb₂O₃, As₂O₃, SnO₂, Na₂SO₄, K₂SO₄, Li₂SO₄, NaNO₃, and KNO₃. In some embodiments, the molar percentage of the clarifying agent in the glass-ceramic is 0.1% to 1%.
[0141] In some possible implementations, the microcrystalline glass, with a thickness of 0.7 mm, has a transmittance of not less than 89% for a wavelength of 550 nm; the elastic modulus of the microcrystalline glass is 115 GPa to 130 GPa; the compressive stress at a depth of 50 micrometers from the surface of the microcrystalline glass is 113 MPa to 165 MPa; and the stress layer depth of the microcrystalline glass is 100 μm to 130 μm.
[0142] The beneficial effects of the above embodiments of this application have been discussed in detail above and will not be repeated here.
[0143] In step S20 above:
[0144] In some possible implementations, the heat treatment of the substrate glass is a one-step heat treatment, involving treatment at temperatures of 620°C to 800°C for 1 to 10 hours. In this case, nucleation (crystal nucleation) and crystallization (crystal growth) processes are completed simultaneously within a single temperature range, eliminating the need for segmented temperature control, simplifying equipment operation, and reducing process complexity. This shortens the total heat treatment time (typically by 30% to 50% compared to a two-step method), making it suitable for mass production, and resulting in lower energy consumption (reduced repeated heating and cooling processes).
[0145] For example, the temperature of the one-step heat treatment can be any typical but non-limiting point value or an interval between any two points, such as 620℃, 650℃, 700℃, 750℃, 800℃, etc., and the duration can be any typical but non-limiting point value or an interval between any two points, such as 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, etc.
[0146] In some possible implementations, the heat treatment of the substrate glass is a two-step process, including treatment at 580°C–660°C for 1–10 hours, followed by treatment at 660°C–800°C for 1–20 hours. In this case, nucleation (forming crystal nuclei) is first performed at a lower temperature, followed by crystallization (crystal growth) at a higher temperature. The nucleation stage temperature is 580°C–660°C, where a long holding time at low temperature forms high-density, fine crystal nuclei. The crystallization stage temperature is 660°C–800°C, where a short high-temperature treatment allows the crystal nuclei to grow into uniform microcrystals. This results in a narrow crystal size distribution, a low proportion of residual glass phase, and improved mechanical strength, thermal stability, and light transmittance of the glass-ceramic. Furthermore, the staged treatment reduces thermal stress concentration, lowers the risk of microcracks and bubble formation, and improves product yield.
[0147] For example, in a two-step heat treatment, the temperature of the first stage can be any typical but non-limiting point value or an interval between any two points, such as 580℃, 590℃, 600℃, 610℃, 620℃, 630℃, 640℃, 650℃, etc., and the duration can be any typical but non-limiting point value or an interval between any two points, such as 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, etc. The temperature in the second stage can be any typical but non-restrictive point value or an interval between any two points, such as 660℃, 680℃, 700℃, 720℃, 740℃, 750℃, 780℃, 800℃, etc., and the duration can be any typical but non-restrictive point value or an interval between any two points, such as 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 12h, 15h, 18h, 20h, etc.
[0148] In some possible implementations, after heat treatment, the process further includes immersing the glass-ceramic sheet in an ion-exchange molten salt to chemically strengthen the glass-ceramic through an ion-exchange process. Enhancing the mechanical properties of the glass-ceramic through ion exchange can also form a compressive stress layer on its surface, thereby improving its impact and scratch resistance; and altering the chemical composition and microstructure of the glass-ceramic surface can further improve its surface properties.
[0149] In some possible implementations, the ion-exchange molten salt includes at least one of NaNO3 molten salt and KNO3 molten salt. The type of alkali metal in the glass composition is related to the ion-exchange molten salt. Generally, Na readily exchanges ions with Li, while K readily exchanges ions with Na; however, the radii of K and Li differ significantly, resulting in poor ion-exchange efficiency. When the glass contains some Na and Li, pure NaNO3 molten salt or a mixture of NaNO3 molten salt and KNO3 molten salt can be used for ion exchange.
[0150] In some possible implementations, the ion exchange process is carried out at a temperature of 340°C to 520°C for a duration of 2 hours to 8 hours. Under these conditions, sufficient chemical strengthening of the glass-ceramic through ion exchange can be ensured. The temperature and duration of the ion exchange process affect the ion exchange effect; low temperatures or short times result in poor strengthening of the glass-ceramic properties. However, excessively high temperatures or excessively long times can also cause relaxation of the glass structure, leading to a decrease in stress and thus poor strengthening of the glass-ceramic.
[0151] For example, the temperature of the ion exchange process can be any typical but non-limiting point value or a range between any two points, such as 340℃, 350℃, 360℃, 380℃, 400℃, 420℃, 450℃, 480℃, 500℃, 520℃, etc., and the duration can be any typical but non-limiting point value or a range between any two points, such as 2h, 3h, 4h, 5h, 6h, 7h, 8h, etc.
[0152] In some possible implementations, the ion exchange process includes the following steps: Preparing a suitable molten salt according to the requirements of ion exchange. Commonly used molten salts include KNO3 and NaNO3, and other auxiliary additives may be added to adjust the ion exchange process. Pre-treating the microcrystalline glass slides, such as cutting, edge grinding, washing, and drying, to ensure dimensional accuracy and surface cleanliness. Immersing the pre-treated microcrystalline glass slides in the molten salt for ion exchange. Parameters such as the ion exchange temperature, time, and molten salt composition need to be adjusted according to the specific microcrystalline glass composition and the required performance. For example, the ion exchange temperature is 340℃~520℃, and the duration is 2h~8h. After ion exchange, the microcrystalline glass slides are removed from the molten salt and cooled. After cooling, the microcrystalline glass slides are washed and dried to remove molten salt residue from the surface.
[0153] Thirdly, embodiments of this application provide a glass device, which is made using the aforementioned microcrystalline glass and / or the aforementioned microcrystalline glass.
[0154] The glass devices in this application utilize the aforementioned microcrystalline glass, which simultaneously possesses high elastic modulus, transmittance, and ion exchange performance. This gives it unique comprehensive advantages among glass devices, making it particularly suitable for scenarios with stringent requirements for mechanical strength, optical performance, and durability. Specifically, the high elastic modulus and high material stiffness reduce bending or deformation of the glass device under stress, making it suitable for manufacturing ultra-thin yet bend-resistant components (such as the hinge cover of a foldable phone). Ion exchange strengthening further enhances impact resistance, achieving a "thin yet strong" design, contributing to the trend of lightweight consumer electronics. High transmittance matches the refractive index of the glass phase, reducing light scattering and meeting the stringent transparency requirements of optical devices. The glass devices in this application, through the integrated characteristics of "strength (high modulus) - transparency (high transmittance) - toughness (strengthable)," overcome the limitations of traditional glass devices (the contradiction between strength and light transmission) or sapphire (high cost and difficult processing), becoming an ideal choice for high-end glass devices and driving innovation and iteration in the fields of electronics, optics, and medicine.
[0155] In some possible implementations, the glass device includes cover glass for electronic products such as smartphones, watches, and tablets. By using microcrystalline glass, which simultaneously possesses high elastic modulus, transmittance, and ion exchange performance, the cover glass exhibits excellent mechanical properties such as drop resistance and scratch resistance.
[0156] Fourthly, embodiments of this application provide an electronic product that includes the aforementioned glass device.
[0157] The electronic products in this application embodiment include the aforementioned glass device, which simultaneously possesses high elastic modulus, transmittance, and ion exchange performance, thereby improving the application safety, stability, and service life of the electronic products.
[0158] In some possible implementations, the electronic product may be a smartphone, watch, tablet, etc., and the cover glass of these electronic products adopts the glass device of the above embodiments of this application.
[0159] Example
[0160] The following description uses specific embodiments. These embodiments are exemplary and are only used to explain this application, and should not be construed as limiting the application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all commercially available conventional products.
[0161] Example 1
[0162] This application provides a microcrystalline glass, which comprises the following components, calculated by molar percentage of oxides: 44% SiO2, 10% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 30% MgO, and 4% TiO2.
[0163] Its preparation includes the following steps:
[0164] 1. Mix the raw materials corresponding to each component in proportion, melt them at a temperature of 1500℃, clarify and homogenize them, and then shape them; then, anneal them at a temperature of 550℃ for 5 hours to obtain the substrate glass.
[0165] 2. The substrate glass is heat-treated at 640℃ for 4 hours and then at 700℃ for 2 hours to crystallize the glass material, thus obtaining the heat-treated glass.
[0166] 3. After cleaning the heat-treated glass, immerse it in NaNO3 ion-exchange molten salt and perform ion exchange at 460℃ for 8 hours to obtain microcrystalline glass.
[0167] Example 2
[0168] This application provides a microcrystalline glass comprising the following components, calculated by molar percentage of oxides: 42% SiO2, 12% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 30% MgO, and 4% TiO2.
[0169] Its preparation includes the following steps:
[0170] 1. Mix the raw materials corresponding to each component in proportion, melt them at a temperature of 1550℃, clarify and homogenize them, and then shape them; then, anneal them at a temperature of 500℃ for 10 hours to obtain the substrate glass.
[0171] 2. The substrate glass is heat-treated at 640℃ for 4 hours, and then at 680℃ for 4 hours to crystallize the glass material, thus obtaining the heat-treated glass.
[0172] 3. After cleaning the heat-treated glass, immerse it in NaNO3 ion-exchange molten salt and perform ion exchange at 480℃ for 6 hours to obtain microcrystalline glass.
[0173] Example 3
[0174] This application provides a microcrystalline glass, which, calculated by the molar percentage of oxides, comprises: 40% SiO2, 14% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 30% MgO, and 4% TiO2.
[0175] Its preparation includes the following steps:
[0176] 1. Mix the raw materials corresponding to each component in proportion, melt them at a temperature of 1620℃, clarify and homogenize them, and then shape them; then, anneal them at a temperature of 600℃ for 5 hours to obtain the substrate glass.
[0177] 2. The substrate glass is heat-treated at 640℃ for 4 hours and then at 700℃ for 2 hours to crystallize the glass material, thus obtaining the heat-treated glass.
[0178] 3. After cleaning the heat-treated glass, immerse it in NaNO3 ion-exchange molten salt and perform ion exchange at 500℃ for 4 hours to obtain microcrystalline glass.
[0179] Example 4
[0180] This application provides a microcrystalline glass, which, calculated by the molar percentage of oxides, comprises: 40% SiO2, 17% Al2O3, 2% Na2O, 14% Li2O, 25% MgO, and 2% TiO2.
[0181] The preparation steps are as described in Example 1.
[0182] Example 5
[0183] This application provides a microcrystalline glass, which, calculated by molar percentage of oxides, comprises: 41% SiO2, 14% Al2O3, 1% Na2O, 14% Li2O, 1% Cs2O, 27% MgO, and 2% TiO2.
[0184] The preparation steps are as described in Example 1.
[0185] Example 6
[0186] This application provides a microcrystalline glass, which, calculated by the molar percentage of oxides, comprises: 40% SiO2, 10% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 34% MgO, and 4% TiO2.
[0187] The preparation steps are as described in Example 2.
[0188] Example 7
[0189] This application provides a microcrystalline glass comprising the following components, calculated by molar percentage of oxides: 41% SiO2, 12% Al2O3, 3% Na2O, 10% Li2O, 1% K2O, 29% MgO, and 4% TiO2.
[0190] The preparation steps are as described in Example 1.
[0191] Example 8
[0192] This application provides a microcrystalline glass, which, calculated by molar percentage of oxides, comprises: 41% SiO2, 12% Al2O3, 1% Na2O, 10% Li2O, 3% K2O, 29% MgO, and 4% TiO2.
[0193] The preparation steps are as described in Example 3.
[0194] Example 9
[0195] This application provides a microcrystalline glass comprising the following components, calculated by molar percentage of oxides: 41% SiO2, 12% Al2O3, 1% Na2O, 10% Li2O, 3% Cs2O, 29% MgO, and 4% TiO2.
[0196] The preparation steps are as described in Example 1.
[0197] Example 10
[0198] This application provides a microcrystalline glass, which comprises the following components, calculated by molar percentage of oxides: 45% SiO2, 10% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 30% MgO, and 4% TiO2.
[0199] The preparation steps are as described in Example 1.
[0200] Example 11
[0201] This application provides a microcrystalline glass, which, calculated by the molar percentage of oxides, comprises: 40% SiO2, 12% Al2O3, 4% Na2O, 10% Li2O, 1% K2O, 29% MgO, and 4% TiO2.
[0202] The preparation steps are as described in Example 1.
[0203] Example 12
[0204] This application provides a microcrystalline glass, which, calculated by the molar percentage of oxides, comprises: 43% SiO2, 15% Al2O3, 1% Na2O, 12% Li2O, 25% MgO, and 4% TiO2.
[0205] The preparation steps are as described in Example 1.
[0206] Example 13
[0207] This application provides a microcrystalline glass comprising the following components, calculated by molar percentage of oxides: 42% SiO2, 11% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 1% Cs2O, 30% MgO, and 4% TiO2.
[0208] The preparation steps are as described in Example 1.
[0209] Example 14
[0210] This application provides a microcrystalline glass comprising the following components, calculated by molar percentage of oxides: 42% SiO2, 11% Al2O3, 1% Na2O, 10% Li2O, 2% Cs2O, 30% MgO, and 4% TiO2.
[0211] The preparation steps are as described in Example 1.
[0212] Example 15
[0213] This application provides a microcrystalline glass, which, calculated by molar percentage of oxides, comprises: 40% SiO2, 10% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 35% MgO, and 3% TiO2.
[0214] The preparation steps are as described in Example 1.
[0215] Example 16
[0216] This application provides a microcrystalline glass, which, calculated by molar percentage of oxides, comprises: 43% SiO2, 10% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 30% MgO, and 5% TiO2.
[0217] The preparation steps are as described in Example 1.
[0218] Comparative Example 1
[0219] This comparative example provides a glass-ceramic comprising, by molar percentage of oxides: 39% SiO2, 15% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 30% MgO, and 4% TiO2.
[0220] The preparation steps are as described in Example 1.
[0221] Comparative Example 2
[0222] This comparative example provides a glass-ceramic comprising, by molar percentage of oxides: 46% SiO2, 10% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 28% MgO, and 4% TiO2.
[0223] The preparation steps are as described in Example 1.
[0224] Comparative Example 3
[0225] This comparative example provides a glass-ceramic comprising, by molar percentage of oxides: 43% SiO2, 9% Al2O3, 2% Na2O, 10% Li2O, 2% K2O, 30% MgO, and 4% TiO2.
[0226] The preparation steps are as described in Example 1.
[0227] Comparative Example 4
[0228] This comparative example provides a glass-ceramic comprising, by molar percentage of oxides: 40% SiO2, 21% Al2O3, 1% Na2O, 11% Li2O, 25% MgO, and 2% TiO2.
[0229] The preparation steps are as described in Example 1.
[0230] Comparative Example 5
[0231] This comparative example provides a glass-ceramic comprising, by molar percentage of oxides: 44.5% SiO2, 10% Al2O3, 0.5% Na2O, 10% Li2O, 1% K2O, 30% MgO, and 4% TiO2.
[0232] The preparation steps are as described in Example 1.
[0233] Comparative Example 6
[0234] This comparative example provides a glass-ceramic comprising, by molar percentage of oxides: 40% SiO2, 11% Al2O3, 5% Na2O, 10% Li2O, 1% K2O, 29% MgO, and 4% TiO2.
[0235] The preparation steps are as described in Example 1.
[0236] Comparative Example 7
[0237] This comparative example provides a glass-ceramic comprising, by molar percentage of oxides: 44% SiO2, 11% Al2O3, 1% Na2O, 9% Li2O, 1% K2O, 30% MgO, and 4% TiO2.
[0238] The preparation steps are as described in Example 1.
[0239] Comparative Example 8
[0240] This comparative example provides a glass-ceramic comprising, by molar percentage of oxides: 41% SiO2, 13% Al2O3, 1% Na2O, 15% Li2O, 1% Cs2O, 27% MgO, and 2% TiO2.
[0241] The preparation steps are as described in Example 1.
[0242] Comparative Example 9
[0243] This comparative example provides a glass-ceramic comprising, by molar percentage of oxides: 40% SiO2, 12% Al2O3, 1% Na2O, 10% Li2O, 4% K2O, 29% MgO, and 4% TiO2.
[0244] The preparation steps are as described in Example 1.
[0245] Comparative Example 10
[0246] This comparative example provides a glass-ceramic comprising, by molar percentage of oxides: 41% SiO2, 17% Al2O3, 2% Na2O, 14% Li2O, 24% MgO, and 2% TiO2.
[0247] The preparation steps are as described in Example 1.
[0248] Comparative Example 11
[0249] This comparative example provides a glass-ceramic comprising, by molar percentage of oxides: 40% SiO2, 10% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 36% MgO, and 2% TiO2.
[0250] The preparation steps are as described in Example 1.
[0251] Comparative Example 12
[0252] This comparative example provides a glass-ceramic comprising, by molar percentage of oxides: 42% SiO2, 14% Al2O3, 1% Na2O, 14% Li2O, 1% Cs2O, 27% MgO, and 1% TiO2.
[0253] The preparation steps are as described in Example 1.
[0254] Comparative Example 13
[0255] This comparative example provides a glass-ceramic comprising, by molar percentage of oxides: 42% SiO2, 10% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 30% MgO, and 6% TiO2.
[0256] The preparation steps are as described in Example 1.
[0257] The molar percentage content of each oxide component in the microcrystalline glass provided in the above embodiments and comparative examples is shown in Table 1 below:
[0258] Table 1
[0259]
[0260]
[0261] The following performance tests were performed on the glass-ceramics in the above embodiments and comparative examples:
[0262] 1. Elastic modulus test: The test was conducted using the method specified in the national standard GB / T 31544-2015.
[0263] 2. CS50 test: The SLP-2000 stress meter was used for testing.
[0264] 3. DOL test: The SLP-2000 stress meter was used for the test.
[0265] 4. Vickers hardness after ion exchange: tested using a Vickers hardness tester with a test force of 200g and a holding time of 10s.
[0266] 5. X-ray diffraction tests were performed on the microcrystalline glass of Example 1, and its XRD pattern is shown in the attached figure. Figure 2 As shown in the figure, it can be seen that the crystallization of Mg2SiO4 was achieved.
[0267] 6. Microcrystalline Glass Transmittance Test: The transmittance of a 0.7 mm thick microcrystalline glass was tested at a wavelength of 550 nm. The transmittance curve of the microcrystalline glass in Example 1 is attached. Figure 3 As shown, the microcrystalline glass has a high transmittance, reaching 90.1% at 550 nm.
[0268] The test results are shown in Table 2 below:
[0269] Table 2
[0270]
[0271]
[0272] As can be seen from the test data in Table 1, the embodiments of this application have achieved a synergistic improvement in the elastic modulus, transmittance and ion exchange performance of microcrystalline glass in glass compositions containing high alkali metal ions by synergistic regulation of the precipitation of high elastic modulus crystalline phase and the residual glass phase structure.
[0273] Example 1 shows that Mg2SiO4 crystallization was achieved, and the glass-ceramic exhibited high transmittance, reaching 90.1% at 550 nm. Example 2 shows that increasing the Al2O3 content enabled the preparation of a glass-ceramic with high elastic modulus, while also improving ion exchange performance. Example 3 shows that increasing the Al2O3 content enabled the preparation of a glass-ceramic with high elastic modulus, while also improving ion exchange performance. Example 4 shows that high contents of both Al2O3 and Li2O improved ion exchange performance. Example 5 shows that high-strength, high-ion-exchange-performance glass-ceramics were prepared using relatively little TiO2. Example 6 shows that MgO significantly affects ion exchange; increasing the MgO content reduces the ion exchange layer depth. Example 7 shows that increasing the Na2O content is beneficial for increasing the ion exchange layer depth. Example 8 shows that increasing the K2O content reduces the elastic modulus. Example 9 shows that increasing the Cs2O content in this example caused a decrease in the elastic modulus of the glass-ceramic. As the contents of Mg2SiO4 and Na2O increase, the depth of the ion exchange layer increases. Example 10 shows that increasing the SiO2 content improves the elastic modulus. Example 11 shows that decreasing the contents of MgO and SiO2 while increasing the contents of Al2O3 and Na2O improves both the elastic modulus and ion exchange performance. Example 12 shows that decreasing the contents of MgO and SiO2 while increasing the contents of Al2O3 and Li2O is beneficial for increasing the depth of the ion exchange layer. Example 13 shows that decreasing the contents of SiO2, increasing the contents of Al2O3, and adding K2O and Cs2O are beneficial for improving both the elastic modulus and ion exchange performance. Example 14 shows that decreasing the contents of SiO2, increasing the contents of Al2O3, and adding only Cs2O has little impact on the performance of the glass-ceramic. Example 15 shows that decreasing the contents of SiO2 and increasing the contents of MgO has little impact on the performance of the glass-ceramic. Example 16 shows that decreasing the contents of SiO2 and increasing the contents of TiO2 has little impact on the performance of the glass-ceramic.
[0274] In Comparative Examples 1 and 2, when the SiO2 content was as low as 39% or as high as 46%, the transmittance of the glass-ceramic decreased, and its ion exchange performance was affected. In Comparative Examples 3 and 4, when the Al2O3 content was as low as 9% or as high as 21%, the transmittance of the glass-ceramic decreased, and its ion exchange performance was affected. In Comparative Examples 5 and 6, when the Na2O content was as low as 0.5% or as high as 5%, both the transmittance and ion exchange performance of the glass-ceramic were affected. In Comparative Examples 7 and 8, when the Li2O content was as low as 9% or as high as 15%, the transmittance of the glass-ceramic decreased significantly, and both its ion exchange performance and exchange depth decreased. In Comparative Example 9, when the K2O content was 4%, the transmittance of the glass-ceramic decreased significantly, and the Vickers hardness decreased after ion exchange. In Comparative Examples 10 and 11, when the MgO content was as low as 24% or as high as 36%, the transmittance of the glass-ceramic decreased, the ion exchange depth decreased, the ion exchange performance deteriorated, and the Vickers hardness decreased significantly after ion exchange. Comparative Examples 12 and 13 show that when the TiO2 content is as low as 1% or as high as 6%, the transmittance of the glass-ceramic is significantly reduced, and the elastic modulus and ion exchange capacity are also reduced.
[0275] Appendix Figure 4 The stress curve of the microcrystalline glass in Example 9 (i.e., the stress curve obtained by testing the sample with SLP-2000 after ion exchange) is obtained under the following ion exchange conditions: pure NaNO3 molten salt, 480℃ / 4h.
[0276] Appendix Figure 5 The curve shows the relationship between the crystallinity of Mg2SiO4 and the depth of the ion exchange layer in the microcrystalline glass of Example 9. It can be seen that after nucleation at 640℃ for 4h, the crystallinity of the microcrystalline glass sample was 10% for 0.5h, 20% for 1h, 30% for 2h, 40% for 3h, and 50% for 5h. Within this range of holding time, the crystallinity of the glass increased with the extension of the holding time.
[0277] Appendix Figure 6 The curves show the relationship between Na2O content and ion exchange layer depth in the microcrystalline glass of Examples 3, 4, 7 and 12. It can be seen that the ion exchange layer depth increases with increasing Na2O content.
[0278] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and not to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. These modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application, and they should all be covered within the scope of the claims and specification of this application. In particular, as long as there is no structural conflict, the various technical features mentioned in the embodiments can be combined in any way. The protection scope of this application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims. Therefore, the protection scope of this application should be determined by the protection scope of the claims.
Claims
1. A microcrystalline glass, characterized in that, The glass-ceramic comprises the following components, calculated as a molar percentage of oxides: The main crystalline phase of the microcrystalline glass does not contain alkali metals.
2. The microcrystalline glass as described in claim 1, characterized in that, The main crystalline phase in the microcrystalline glass includes Mg2SiO4.
3. The microcrystalline glass as described in claim 1, characterized in that, The average grain size of the crystalline phase in the microcrystalline glass is no higher than 50 nm; And / or, the crystallinity of the microcrystalline glass is 35% to 60%.
4. The microcrystalline glass according to any one of claims 1 to 3, characterized in that, In the microcrystalline glass, the absolute difference between the molar percentage of Al2O3 and the total molar percentage of alkali metal oxides is not higher than 2%, and the alkali metal oxides include Li2O, Na2O, K2O and Cs2O; And / or, in the microcrystalline glass, the ratio of Na2O to Li2O is greater than 0 and not higher than 0.3; And / or, in the microcrystalline glass, the ratio of MgO to SiO2 is not less than 0.6 and not more than 1.
5. The microcrystalline glass as described in claim 4, characterized in that, The glass-ceramic comprises the following components, calculated as a molar percentage of oxides: 44% SiO2, 10% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 30% MgO, 4% TiO2; Alternatively, 42% SiO2, 12% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 30% MgO, and 4% TiO2. Alternatively, 40% SiO2, 14% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 30% MgO, and 4% TiO2. Alternatively, 40% SiO2, 17% Al2O3, 2% Na2O, 14% Li2O, 25% MgO, and 2% TiO2; Alternatively, 41% SiO2, 14% Al2O3, 1% Na2O, 14% Li2O, 1% Cs2O, 27% MgO, and 2% TiO2. Alternatively, 40% SiO2, 10% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 34% MgO, and 4% TiO2. Alternatively, 41% SiO2, 12% Al2O3, 3% Na2O, 10% Li2O, 1% K2O, 29% MgO, and 4% TiO2; Alternatively, 41% SiO2, 12% Al2O3, 1% Na2O, 10% Li2O, 3% K2O, 29% MgO, and 4% TiO2; Alternatively, 41% SiO2, 12% Al2O3, 1% Na2O, 10% Li2O, 3% Cs2O, 29% MgO, and 4% TiO2. Alternatively, 45% SiO2, 10% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 30% MgO, and 4% TiO2. Alternatively, 40% SiO2, 12% Al2O3, 4% Na2O, 10% Li2O, 1% K2O, 29% MgO, and 4% TiO2; Alternatively, 43% SiO2, 15% Al2O3, 1% Na2O, 12% Li2O, 25% MgO, and 4% TiO2; Alternatively, 42% SiO2, 11% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 1% Cs2O, 30% MgO, and 4% TiO2. Alternatively, 42% SiO2, 11% Al2O3, 1% Na2O, 10% Li2O, 2% Cs2O, 30% MgO, and 4% TiO2. Alternatively, 40% SiO2, 10% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 35% MgO, and 3% TiO2. Alternatively, 43% SiO2, 10% Al2O3, 1% Na2O, 10% Li2O, 1% K2O, 30% MgO, and 5% TiO2.
6. The microcrystalline glass according to any one of claims 1 to 5, characterized in that, The microcrystalline glass also includes a clarifying agent.
7. The microcrystalline glass as described in claim 6, characterized in that, The clarifying agent includes at least one of Sb2O3, As2O3, SnO2, Na2SO4, K2SO4, Li2SO4, NaNO3, and KNO3; And / or, in the microcrystalline glass, the molar percentage content of the clarifying agent is 0.1% to 1%.
8. The microcrystalline glass according to any one of claims 1 to 7, characterized in that, The microcrystalline glass, with a thickness of 0.7 mm, has a transmittance of not less than 89% for a wavelength of 550 nm. And / or, the elastic modulus of the microcrystalline glass is 115 GPa to 130 GPa; And / or, the compressive stress at a depth of 50 micrometers from the surface of the microcrystalline glass is 113 MPa to 165 MPa; And / or, the stress layer depth of the microcrystalline glass is 100μm to 130μm.
9. A method for preparing microcrystalline glass, characterized in that, Includes the following steps: The raw materials, calculated by the molar percentage of oxides, include 40%–45% SiO2, 10%–17% Al2O3, 10%–14% Li2O, 1%–4% Na2O, 0%–3% K2O, 0%–3% Cs2O, 25%–35% MgO, and 2%–5% TiO2. These components are then mixed to form a substrate glass. The substrate glass is heat-treated to crystallize it, resulting in a microcrystalline glass, wherein the main crystalline phase of the microcrystalline glass does not contain alkali metals.
10. The method for preparing microcrystalline glass according to claim 9, characterized in that, The melting temperature for preparing the substrate glass is 1400℃~1650℃; And / or, the annealing conditions for preparing the substrate glass include: annealing at a temperature of 450℃~650℃ for 1h~10h; And / or, the heat treatment is a one-step heat treatment, including treatment at a temperature of 620℃~800℃ for 1h~10h; Alternatively, the heat treatment is a two-step heat treatment, including treatment at a temperature of 580℃~660℃ for 1h~10h, followed by treatment at a temperature of 660℃~800℃ for 1h~20h.
11. The method for preparing microcrystalline glass as described in claim 9 or 10, characterized in that, After the heat treatment, the process further includes immersing the microcrystalline glass sheet in an ion-exchange molten salt to chemically strengthen the microcrystalline glass through an ion-exchange process.
12. The method for preparing microcrystalline glass according to claim 11, characterized in that, The ion-exchange molten salt includes at least one of NaNO3 molten salt and KNO3 molten salt; And / or, the temperature of the ion exchange process is 340℃~520℃, and the duration is 2h~8h.
13. A glass device, characterized in that, The glass device is made of the microcrystalline glass as described in any one of claims 1 to 8 and / or the microcrystalline glass as described in any one of claims 9 to 12.
14. An electronic product, characterized in that, The electronic product includes the glass device as described in claim 13.